CableAuth: a biometric second factor authentication scheme for electric vehicle charging - Sturgess, J; Köhler, S; Birnbach, S; Martinovic, I (Internet Society, 2023)
Electric vehicle charging sessions can be authorised in different ways, ranging from smartphone applications to smart cards with unique identifiers that link the electric vehicle to the charging station. However, these methods do not provide strong authentication guarantees. In this paper, we propose a novel second factor authentication scheme to tackle this problem. We show that by using inertial sensor data collected from IMU sensors either embedded in the handle of the charging cable or on a separate smartwatch, users can be authenticated implicitly by behavioural biometrics as they unhook the cable from the charging station and plug it into their car at the start of a charging session. To validate the system, we conducted a user study (n=20) to collect data and we developed a suite of authentication models for which we achieve EERs of 0.06.